Benefits, Risk Factors and Cognitive Insights for Improving the Well-being of Minors in Greek Foster Care - Farmakopoulou, Ignatia; Baltsioti, Vasiliki (Technium Education and Humanities, 2024)
This research paper presents a holistic analysis of the foster care system in Greece, exploring its historical evolution, legal nuances, practical concerns, and the recent legislative reforms aimed at improving the well-being of minors in foster care. The study examines various types of foster care arrangements—kinship, non-relative, and professional fostering—highlighting their impact on the psychological, social, and cognitive development of children. It underscores the crucial role of foster families and social workers in providing a conducive family environment, while also cataloging the potential drawbacks of the system, including professional intervention challenges, emotional and social strain on the children, and gaps in the fostering infrastructure. By comparing the Greek fostering institution with systems in France, Germany, Denmark, Italy, and Ireland, the paper identifies unique challenges and best practices, contributing to an understanding of international foster care dynamics. The research also delves into the intricacies of adoption versus fostering, detailing the emotional and legal commitments involved. Furthermore, the paper integrates insights from related studies on trauma, mental health, and educational neuroscience, providing a multidisciplinary perspective on the needs of foster children. It illustrates the promising strides made by initiatives like the Child Guarantee program to fight poverty and exclusion, emphasizing the need for targeted policies and legislative action. Toward its conclusion, the research accentuates the call for ongoing interdisciplinary studies, policy refinements, and improved professional training within Greek child welfare systems. It presents a compelling case for robust, trauma-informed care frameworks and legislation designed to secure the best outcomes for vulnerable children in foster care.